Family economics education and basic economics in shaping students’ irrationality - Albrian Fiky Prakoso; Waspodo Tjipto Subroto; Eka Hendi Andriansyah; Norida Canda Sakti; Ardhita Eko Ginanjar; Prattana Srisuk; Dyah Nugraheny Priastuti; Ety Youhanita (International Journal of Evaluation and Research in Education (IJERE), 2026)
The COVID-19 pandemic has led to changes in consumption habits and irrational consumption, which also exhibit a strong tendency towards family economic education (FEE) in shaping student economic behavior and economic irrationality (IR). The novelty of this study lies in the exploration of the relationship between FEE and students’ economic behavior mediated by basic economic (BE) understanding, which is still under-explored in the context of economic education in Indonesia. This study uses a quantitative approach with structural equation modeling (SEM). A total of 385 students of economics or economic education study programs are spread across 38 provinces in Indonesia. The finding of the research indicate that FEE has a significant but relatively weak positive effect on students’ BE understanding. In addition, FEE directly increases students’ irrationality, as well as BE understanding, which also turns out to contribute positively to such irrational behavior. This finding implicitly shows that the delivery of intensive FEE information does not always have a positive impact but can actually strengthen IR in students. Thus, this study emphasizes the need for a more careful and selective approach in FEE to reduce students’ irrational behavior.